An Audit on the implementation of administering Ondansetron in children with acute gastroenteritis and its effect on admission rate - D’Sa, Saskia; Hussain, Ahad; Hussain, Mushtaq; Afridi, Zahir; Twomey, John; Ahmed, Irfan (Journal of Advanced Pediatrics and Child Health, 2021)
cute gastroenteritis (AGE) is a common presenting complaint in paediatrics. Most often, the reason for admission into hospital is to initiate intravenous rehydration in patients with severe dehydration and inability to tolerate oral intake. We found that Ondansetron acts as a potent antiemetic to support an increased number of children receiving oral hydration, and subsequently leading to decreased rates of admission. This study aims to audit the use of Ondansetron to Oral Rehydration Therapy (ORT) on children with acute gastroenteritis, and its effect on admission rates from the emergency department in University Hospital, Limerick (UHL). Data collected over a 3-month period from June to August 2017 in which Ondansetron was not used was compared to another 3-month period when Ondansetron was used. Several outcomes were measured including admission to hospital. The rate of admission decreased by 15% [26/74 (35%) in 2017 to 16/81 (20%) in 2019 p = 0.22]. 81 patients received Ondansetron, of which 79% were successfully rehydrated orally. The administration of Ondansetron reduced the need for intravenous fluids and hospital admission overall in these children with AGE. This reduction ultimately accounted for lower costs incurred by the Health Services Executive per patient, and also suggested the anti-emetic use as a cost effective measure for managing and treating patients with AGE.